The effect of different kinetin concentration on shoot multiplication of Clinacanthus nutans node culture - Zakaria, Nur Syazwani (2018)
Clinacanthus nutans also known as Sabah Snake Grass is a herb originated from Malaysia, Thailand and China belonging to the Acanthaceae family. This plant is a shrub with terete and glabrescent stems. It has a simple leaf arranged in an opposite manner with its shape lanceolate to ovate. This plant is traditionally used for disease treatment such as skin rashes, allergic and burns as well in curing snakebites. Recent research shows it is also efficiently used as remedies for herpes simplex and VZV lesions and alternative to cure cancer. The common method to propagate this plant is through stem cuttings, which requires much labour and time consuming and with limited number of planting materials produced. Therefore, tissue culture can be an alternative method to produce large number of offspring within a smaller space and short period of time. This experiment is carried out in In Vitro Laboratory, Department of Agriculture, UPM to determine the best concentration of kinetin that can maximize in vitro shoot proliferation from Clinacanthus nutans node culture. The experiment is carried out using Completely Randomised Design (CRD) with 7 treatments and 12 replications. Nodes (1cm) are excised from axenic cultures of Clinacanthus nutans and cultured at a slanting position in Murashige and Skoog (1962) medium with supplemented with different concentration of kinetin (0, 1.0, 2.0, 4.0, 6.0, 8.0 and 10.0mg/L). The culture is incubated for 8 weeks in the culture room. It is observed that all kinetin treatments including the control treatment proliferated buds within the range of 83-100%. However, elongation of explant are higher in 1.0mg/L and 2.0mg/L kinetin compared with explant supplemented with 8.0mg/L and 10.0mg/L kinetin. This showed that, higher concentration of kinetin can inhibit explant growth.